APLIKASI HIDROGEN PEROKSIDA DI SEDIMEN TERHADAP KUALITAS AIR DAN PERTUMBUHAN UDANG VANAME Litopenaeus vannamei - Wiyoto, Wiyoto; Yudha Wisesa, Satrio; Lesmanawati, Wida; Muarif, Muarif; Iskandar, Andri; Hendriana, Andri; Indriastuti, Cecilia Eny; Mulya, Muhammad Arif; Ramadhani, Dian Eka; Kusumanti, Ima; Firdausi, Amalia Putri; Lesmana, Dudi (JURNAL MINA SAINS, 2023)
Pond bottom sediment conditions influence shrimp culture. As benthic organisms, shrimp are mainly on the surface of the pond bottom, so cultivation preparations related to improving sediment quality are essential. Pond bottom practice, such as drying, liming, and fertilizing, is common. However, in bottom pond conditions where total drying cannot be carried out, other treatments are needed, such as the addition of hydrogen peroxide. The purpose of this study was to determine the effect of adding hydrogen peroxide in pond sediments on the performance of shrimp growth and water quality. The study was conducted with five doses of hydrogen peroxide (0.25 mL, 0.5 mL, 1 mL, 2 mL) mixed with 350 g of pond soil sediment. Ten shrimps with an average weight of 0,27±0,03 g were put into the rearing container, which had been given pond bottom sediment according to the treatment. The results showed that the 2 mL hydrogen peroxide treatment gave the best results on the growth rate and average weight of Pacific whiteleg shrimp at the end of rearing. Water quality such as pH value, dissolved oxygen, and temperature were not significantly different between treatments. Hydrogen peroxide treatment can improve shrimp growth performance without affecting water quality during rearing.